IFPRI Database for GHG Emissions from Agriculture by Country, Commodity, and Source, 2016 - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This new database of emissions in agricultural production provides data on emissions by type, commodity, source, and country. Wherever possible, this matrix was derived by reverse-engineering the Food and Agriculture Organization (FAO) emission data to ensure that the total matched the FAOSTAT. Where this was not possible, as in the case of emissions from pesticides, a similar Intergovernmental Panel on Climate Change (IPCC) Tier 1 methodology was used to generate comparable estimates. Emission sources are identified used eleven FAOSTAT-based categories plus emissions from agricultural pesticides. The first step was to define the activity levels associated with commodity outputs, such as the area used for rice cultivation. The second was to calculate the emission coefficients (EC) for CH4, CO2, and N2O by activity level using, wherever possible, the FAOSTAT database. Finally, emissions of N2O and CH4 were converted to CO2 equivalents using 310 and 21 for N2O and CH4 respectively.